Extraction and Separation Studies of Th(IV) from Salicylate Media Using Neutral Organophosphorous Extractant - M. GHAG, SNEHAL; D. PAWAR, SURESH (Asian Journal of Chemistry, 2010)
The neutral extractant, Cyanex-923 has been used for the extraction and separation of Th(IV) from sodium salicylate media. The metal ion was found to be quantitatively extracted with Cyanex-923 in toluene at pH 7.0 and from the organic phase they can be stripped with 2.0 M HClO4 solution. The effect of pH, sodium salicylate concentration, reagent concentration, equilibration period, diluents, diverse ions and stripping agent on the extraction of Th(IV) has been studied. The stoichiometry of the extracted species of this metal ion was determined on the basis of the slope analysis method. The reaction proceed by solvation and the probable extracted species found were Th(Sal)2. 2Cyanex-923.